Circularly Polarized Light-Enabled Chiral Nanomaterials: From Fabrication to Application - Hao, Changlong; Wang, Gaoyang; Chen, Chen; Xu, Jun; Xu, Chuanlai; Kuang, Hua; Xu, Liguang (Nano-Micro Letters, 2023)
For decades, chiral nanomaterials have been extensively studied because of their extraordinary properties. Chiral nanostructures have attracted a lot of interest because of their potential applications including biosensing, asymmetric catalysis, optical devices, and negative index materials. Circularly polarized light (CPL) is the most attractive source for chirality owing to its high availability, and now it has been used as a chiral source for the preparation of chiral matter. In this review, the recent progress in the field of CPL-enabled chiral nanomaterials is summarized. Firstly, the recent advancements in the fabrication of chiral materials using circularly polarized light are described, focusing on the unique strategies. Secondly, an overview of the potential applications of chiral nanomaterials driven by CPL is provided, with a particular emphasis on biosensing, catalysis, and phototherapy. Finally, a perspective on the challenges in the field of CPL-enabled chiral nanomaterials is given. Highlights: 1 This review summarized the fabrication strategy using circularly polarized light as a chiral source to construct chiral materials. 2 The potential applications of chiral nanomaterials driven by circularly polarized light in different fields are summarized, explained by representative examples. 3 The potential challenges of circularly polarized light-enabled chiral materials are outlined and future research directions are outlooked.